Circulating Vascular Basement Membrane Fragments are Associated with the Diameter of the Abdominal Aorta and Their Expression Pattern is Altered in AAA Tissue. (July 2018) - Holsti, Mari; Wanhainen, Anders; Lundin, Christina; Björck, Martin; Tegler, Gustaf; Svensson, Johan; Sund, Malin
Abstract : Objective: Abdominal aortic aneurysm (AAA) is characterised by enhanced proteolytic activity, and extracellular matrix (ECM) remodelling in the vascular wall. Type IV and XVIII collagen/endostatin are structural proteins in vascular basement membrane (VBM), a specialised ECM structure. Here the association between plasma levels of these collagens with the aortic diameter and expansion rate is studied, and their expression in aortic tissue characterised. Methods: This was a retrospective population based cohort study. Type IV and XVIII collagen/endostatin were analysed in plasma by ELISA assay in 615 men, divided into three groups based on the aortic diameter: 1) normal aorta ≤ 25 mm, 2) sub-aneurysmal aorta (SAA) 26–29 mm, and 3) AAA ≥ 30 mm. Follow up data were available for 159 men. The association between collagen levels and aortic diameter at baseline, and with the expansion rate at follow up were analysed in ordinal logistic regression and linear regression models, controlling for common confounding factors. Tissue expression of the collagens was analysed in normal aorta ( n = 6) and AAA ( n = 6) by immunofluorescence. Results: Plasma levels of type XVIII collagen/endostatin (136 ng/mL [SD 29] in individuals with a normal aorta diameter, 154 ng/ml [SD 45] in SAA, and 162 ng/ml [SD 46] in AAA; p = .001) and type IV collagen (105 ng/mL [SD 42] normal aorta, 124 ng/ml [SD 46] SAA, and 127 ng/ml [SD 47] AAA; p = .037) were associated with a larger aortic diameter. A significant association was found between the baseline levels of type XVIII/endostatin and the aortic expansion rate ( p = .035), but in the multivariable model, only the initial aortic diameter remained significantly associated with expansion ( p = .005). Altered expression patterns of both collagens were observed in AAA tissue. Conclusion: Plasma levels of circulating type IV and XVIII collagen/endostatin increase with AAA diameter. The expression pattern of VBM proteins is altered in the aneurysm wall.